Trained Immunity in Primary Sjögren’s Syndrome: Linking Type I Interferons to a Pro-Atherogenic Phenotype - Huijser, Erika; van Helden-Meeuwsen, Cornelia G.; Grashof, Dwin G. B.; Tarn, Jessica R.; Brkic, Zana; Huisman, Josje M. A.; Wahadat, M. Javad; van de Werken, Harmen J. G.; Lopes, Ana P.; van Roon, Joel A. G.; van Daele, Paul L. A.; Kamphuis, Sylvia; et al. (Frontiers in Immunology, 2022)
Background Trained immunity – or innate immune memory – can be described as the long-term reprogramming of innate immune cells towards a hyperresponsive state which involves intracellular metabolic changes. Trained immunity has been linked to atherosclerosis. A subgroup of patients with primary Sjögren’s syndrome (pSS) exhibits systemic type I interferon (IFN) pathway activation, indicating innate immune hyperactivation. Here, we studied the link between type I IFNs and trained immunity in an in vitro monocytic cell model and peripheral blood mononuclear cells (PBMCs) from pSS patients. Methods The training stimuli heat killed Candida albicans, muramyl dipeptide, IFNβ, and patient serum were added to THP-1 cells for 24 hours, after which the cells were washed, rested for 48 hours and subsequently re-stimulated with LPS, Pam3Cys, poly I:C, IFNβ or oxLDL for 4-24 hours. PBMCs from pSS patients and healthy controls were stimulated with LPS, Pam3Cys, poly I:C or IFNβ for 0.5-24 hours. Results Training with IFNβ induced elevated production of pro-atherogenic cytokines IL-6, TNFα and CCL2, differential cholesterol- and glycolysis-related gene expression, and increased glucose consumption and oxLDL uptake upon re-stimulation. Type I IFN production was increased in Candida albicans- and IFNβ-trained cells after LPS re-stimulation, but was reduced after poly I:C re-stimulation. Training with muramyl dipeptide and IFNβ, but not Candida albicans, affected the IFN-stimulated gene expression response to IFNβ re-stimulation. PBMCs from pSS patients consumed more glucose compared with healthy control PBMCs and tended to produce more TNFα and type I IFNs upon LPS stimulation, but less type I IFNs upon poly I:C stimulation. Conclusions Type I IFN is a trainer inducing a trained immunity phenotype with pro-atherogenic properties in monocytes. Conversely, trained immunity also affects the production of type I IFNs and transcriptional response to type I IFN receptor re-stimulation. The phenotype of pSS PBMCs is consistent with trained immunity. This connection between type I IFN, trained immunity and cholesterol metabolism may have important implications for pSS and the pathogenesis of (subclinical) atherosclerosis in these patients.